2020
DOI: 10.3354/esr01004
|View full text |Cite
|
Sign up to set email alerts
|

Investigating maternity roost selection by northern long-eared bats at three sites in Wisconsin

Abstract: One of the North American bat species most impacted by white-nose syndrome (WNS) is the northern long-eared bat Myotis septentrionalis, which as a result has been listed under the Endangered Species Act. WNS was first detected in Wisconsin in 2014. Unfortunately, little is known regarding the ecology of M. septentrionalis in this state pre-WNS to guide management supporting post-WNS recovery efforts. The objectives of our research were to (1) assess characteristics of trees that are associated with roost tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…A roosting area of 88.4 ha for the maternity colony on Long Island was more than that observed in studies in Canada, West Virginia, Kentucky, and Wisconsin (min-max = 0.39-58.5 ha; Henderson and Broders 2008, Silvis et al 2015a, Hyzy et al 2020. Smaller roosting areas could reflect short tracking periods (i.e., if bats were not followed long enough to identify the entire scope of their inter-roost movements) or result from "condensed" but superior habitat in terms of roost availability and foraging conditions (Ford et al 2016;Johnson et al 2009.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A roosting area of 88.4 ha for the maternity colony on Long Island was more than that observed in studies in Canada, West Virginia, Kentucky, and Wisconsin (min-max = 0.39-58.5 ha; Henderson and Broders 2008, Silvis et al 2015a, Hyzy et al 2020. Smaller roosting areas could reflect short tracking periods (i.e., if bats were not followed long enough to identify the entire scope of their inter-roost movements) or result from "condensed" but superior habitat in terms of roost availability and foraging conditions (Ford et al 2016;Johnson et al 2009.…”
Section: Discussionmentioning
confidence: 75%
“…The demonstrated longevity, hardness, and rot-resistance of Black Locust (Adams and Owens 2001, Cuno 1930, Ford et al 2006, Meier 2022, coupled with its reputation for cavity formation (Carey 1983, McComb andMuller 1983), may make it the ideal roost for the species, as its presence may be dependable year after year, and there may be several cavity options on the bole itself. Other studies of maternity roosts of Northern Long-eared Bats reported a selection for Black Locust, particularly in areas where it was abundant (Ford et al 2006, Hyzy et al 2020, Johnson et al 2009. The clustering of Black Locust directly opposite other species on the PCA plots suggests that female Northern Long-eared Bats identify and may be selecting specific roosts that provide optimal thermoregulatory conditions (Garroway and Broders 2008, Patriquin et al 2010, Silvis et al 2015a, Thalkin and Lacki 2017.…”
Section: Discussionmentioning
confidence: 84%
“…On many landscapes, remaining WNS-impacted bat populations are now even more patchily distributed on the landscape (Nocera et al 2020). Our WNS impact map could serve as a tool to guide future summer monitoring efforts by highlighting those areas with a greater likelihood to host remaining northern long-eared bat populations or at minimum provide areas where natural history and ecological data could be obtained prior to WNS-caused declines (Hyzy et al 2020). Given the rarity of Myotis species across the landscape, summer sampling needs to be optimized to maximize chances of detection when present.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Female northern long-eared bats form maternity colonies in forests during the spring and summer that integrate multiple day-roosts in trees and snags into a multi-node network within a discrete area , Hyzy et al 2020a). Due to large population declines from WNS impacts, documenting northern long-eared bat presence via mist-netting has become more difficult (Reynolds et al 2016).…”
Section: Introductionmentioning
confidence: 99%